1982
DOI: 10.1002/star.19820340303
|View full text |Cite
|
Sign up to set email alerts
|

Cereal‐ and Root Starch Modification by Heat‐Moisture Treatment. II. Functional Properties and Baking Potential

Abstract: Functional baking properties of heat‐moisture treated starches (barley, triticale, red millet, arrowroot, cassava) described in preceding paper* are given. The bread and cake baking potential of cereal starches was adversely affected by the treatment. Although the quality of breads and cakes failed to match that of untreated wheat starch, the treatment improved tuber starches, suggesting that the molecular order of starches is an important factor in starch baking quality. Thickening properties tested with pie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 2 publications
1
26
0
Order By: Relevance
“…Pre-gelatinization and heat-moisture treatment have been applied in improvement of bread texture as anti-staling agents (Lorenz and Kulp, 1981;Purhagen et al, 2008), and pre-gelatinized flours obtained by steam treatment, as in this study, may also have potential in texture modification for bakery products.…”
Section: Solubility and Swelling Powermentioning
confidence: 82%
“…Pre-gelatinization and heat-moisture treatment have been applied in improvement of bread texture as anti-staling agents (Lorenz and Kulp, 1981;Purhagen et al, 2008), and pre-gelatinized flours obtained by steam treatment, as in this study, may also have potential in texture modification for bakery products.…”
Section: Solubility and Swelling Powermentioning
confidence: 82%
“…This suggests that the dough containing HMT-M caused the decrease of elasticity. Lorenz and Kulp (1981) reported that HMT potato starch did not bind readily with gluten to form dough when it was used for breadmaking. This result shows that HMT-M also does not bind readily with gluten to form elastic dough.…”
Section: Dsc Results Of Hmt-mmentioning
confidence: 98%
“…Kurahashi and Hizukuri (1998) examined rheological properties of HMT maize or wheat starch suspension in oil, and reported that heat-moisture treatment improved emulsifying activity. Lorenz and Kulp (1981) studied functional properties and baking potential of HMT wheat and potato starches with reconstituted flour, and reported that bread or cake quality of wheat starch was deteriorated by the heat-moisture treatment, but that of potato was improved. Heat-moisture treatment can ideally apply to every starch, but little work 0963-9969/$ -see front matter Ó 2004 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%
“…However, the type and extent of change depends on the botanical origin (e.g. cereal, tuber, root or legume), starch composition (e.g., amyloseamylopectin ratio and lipid content) and treatment conditions (temperature, moisture and duration of heating) (Abraham, 1993;Adebowela el aI., 2005aAdebowela el aI., , 2005bAdebowela el aI., , 2005cAdebowela el aI., , 2003Anderson el aI., 2002;Anderson and Guraya, 2006;Chung el aI., 2009aChung el aI., , 2009bBrumovsky el al., 2009;Brumovsky and Thompson, 2001;Collado and Corke, 1999;Collado el al., 2001;Donova el al., 1983;Eerlingenelal., 1996Eerlingenelal., , 1997Franco elal., 1995;Gunaratneand Hoover, 2002;Gunaratne and Corke, 2007;Hoover, 2010;Hoover and Manuel 1996;Vasanthan, 1994a, 1994b;Hoover el al., 1994;Jacobs and Delcour, 1998;Kawabata el al., 1994;Kurakake el al., 1996;Kweon el aI., 2000;Kulp and Lorenz, 1983;Lawai, 2005;Lawai and Adebowale, 2005;Lim et aI., 2001;Lorenz and Kulp, 1981, 1982Lu et al, 1996;Moorthy, 1999;Olayinka, elal., 2008;Pereraelai., 1997;Hoover, 1998,1999;Purwanielal.,2006;Sang and Seib,2006;SchierbaumandKettlitz, 1994;Singhelal., 2009;Stute,1992;…”
Section: Chairmentioning
confidence: 99%